A impolidez no discurso político como encorajamento da violência verbal - Valenzuela, Gabriela Viviana Barrueco (2021)
This study aims to analyze the impoliteness in the responses of the current president of Brazil, Jair Messias Bolsonaro, and the verbal violence on social networks after his statements. We aim to point out the linguistic mechanisms that he uses in order to preserve his own face and threaten the other person’s face. We will also point out the disinhibition of Internet users when reacting to such manifestations. We intend, therefore, to analyze the communicative intentions of the impoliteness strategies used by the president; such as retention and taking turns, change of correction, use of imperatives and bad words; as well as its effects on verbal interaction and social behavior within social networks. This research is based on a socio-international approach to the spoken language, and the corpus is composed of interviews given by Bolsonaro to the press and the comments of internet users posted on social networks where they circulate. The theoretical framework is based on the principles of Conversation Analysis (MARCUSCHI, 1986); (KERBRAT-ORECCHIONI, 2006) and (KOCH 2015, 2016), as well as on the theory of face coined by Goffman (1967), on Brown and Levinson’s study of politeness (1987 [1978]), studies on verbal violence Fuentes Rodríguez e Alcaide Lara (2008), Bousfield (2008) and Culpeper (1996, 2005, 2011) and on Recuero’s researches on online networks (2014, 2018). Regarding the structure, this work is composed of four sections: in section one, we present issues pertinent to the spoken language and the organization of the conversation; the second section deals with the characteristics of digital interaction; the third of Face and Impoliteness. In the fourth section, we describe the methodology, constitution of the corpus, analysis and discussion of the data. Finally, we present the final considerations regarding the research. According to the results, we found that the dimension of the posture and behavior of political authorities, in relation to the planning of their speeches in front of a large audience, can cause a great influence of their supporters. Currently with the advent of online social networks, people have access to a lot of information, not only as spectators, but as disseminators of truths and lies, of harmony and violence and that, many times, only reproduce the speech of the influencer, reinforcing and propagating aggressiveness and prejudices. We also show that Bolsonaro, in trying to preserve an image that he does not want to be exposed to, when questioned on some subjects, uses impoliteness resources as a defense with great frequency.